PREFERENSI PENGUNJUNG MENGENAI SERVICES CAPE THE HOUSE OF RAMINTEN YOGYAKARTA - Sri Sulartiningrum; Muhammad Baiquni; Sri Widodo; Tri Widodo (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2015)
Service cape has an important role in the progress of the company's relationships with customers and employees, products and services in design as one that gives a certain image so as to attract the impression or the initial reaction to give consumer expectations. This research uses descriptive method population is taken from The House Of Raminten, and the sample is 100 people. The sampling technique used is convenience non probabilities sampling. Data were analyzed using descriptive descriptive analysis. The results showed the highest ranking of the value of 87,8% in the uniform of the employee similar of the theme and the lowest ranking of the value of 23,9% in the parking lot.Keywords: Services cape, Ethnic Restaurant